(NsOBRANIE SO^INENIJ W ^ETYREH TOMAH(B; s (NdON(B-(NvUAN(B: [(NpO\MA(B] / s (N~ASTX (B1s - (NbAJRON(B, (NdVORDV gORDONs ((NmOSKWA(B: s (NpRAWDA(B, s, 1981)
(Nw PERWYJ TOM WO[EL (B"(NdON(B-(NvUAN(B" - (NPOSLEDNEE PROIZWEDENIE bAJRONA (B(1788-1824), (NPRINES[EE EMU MIROWU@ SLAWU(B.s
rus
Keywords: (NpO\ZIQ(B, (NPO\MYs; (NrOMAN W STIHAHs